Catalysts of Connectedness: Three Wellsprings of Jewish Culture and Their Effects on Jewish Cultural Identity - Bankier-Karp, Adina Leah (Review of religious research, 2023)
Jewish identification and engagement have cultural as well as religious salience. Jewish cultural engagement, however, is overwhelmingly circumscribed as a fait accompli, often an outcome, rarely a predictor in quantitative examinations of contemporary Jewish life. Consequently, the sociological understanding of Jewish cultural identity formation is limited. This study examines Jewish cultural identity formation in young Australian Jews, identifying roles played by three wellsprings, or sources of Jewish culture. Using the Gen17 Australian Jewish Community Survey 2018, the most recent nationally representative study of Australian Jewry, relationships between Jewish day school education, communal engagement, cultural upbringing, and cultural identity were analyzed using linear and OLS regression models. Jewish day school education significantly affected cultural identity; without mediating effects of communal engagement, however, day school education’s effects were inconsequential. High-level cultural upbringing had amplifying effects, while low-level cultural upbringing had attenuating effects on associations between Jewish day school education and cultural identity. The cultural identity formation mechanism was similar to a proposed religious identity formation mechanism. These results highlight interconnected and indirect effects of cultural wellsprings on identity formation, and similarities between cultural and religious identity formation, with implications for scholars of culture and religion.